Differential Circulating Fungal Microbiome in Prostate Cancer Patients Compared to Healthy Control Individuals. (3rd February 2022) - Wang, Xu; Zhou, Zejun; Turner, David; Lilly, Michael; Ou, Tongwen; Jiang, Wei
Abstract : Backgrounds . Infection and inflammation play an important role in prostate cancer (PCa) etiology and pathogenesis. However, the environmental drivers for PCa are not fully understood. Methods . In a cross-sectional study, we analyzed circulating fungal microbiome in plasma samples from age and race-matched healthy control men (n = 34 ) and preoperative PCa patients (n = 31 ). Results . The fungal community in the plasma exhibited differences between individuals with PCa and healthy controls according to the beta diversity; there was no difference in the alpha diversity. Moreover, the relative abundance of several fungi differed between the two study groups from the class to species levels. The most significant differences were Filobasidiales family, Pyronemataceae family, and Cryptococcus ater species, which were enriched in PCa patients compared to controls. The increased Bipolaris genus was associated with low prostate-specific antigen (PSA) levels, increased Sordariomycetes class was associated with severe pathological stage, and decreased Phoma herbarum species was associated with disease relapse, compared to corresponding controls. Several fungi from class to species levels were increased in the controls compared to patients. Conclusion . This is the first study to show plasma distinct fungal microbiome and its associations with PSA levels, relapse, and pathology stages in PCa patients.